Electrochromic Switching Mechanism of Iron Hexacyanoferrates Molecular Compounds: The Role of Fe2+(CN)(6) Vacancies - Bueno, Paulo Roberto [UNESP]; Gimenez-Romero, David; Ferreira, Fabio Furlan; Setti, Grazielle Oliveira [UNESP]; Juan Garcia-Jareno, Jose; Agrisuelas, Jeronimo; Vicente, Francisco (Amer Chemical Soc, 2009)
On the basis of the structure of electrochemically prepared hexacyanometallate compounds, which was determined very recently and unexpectedly to be an insoluble structure (Bueno, P. R.; et al. J. Phys. Chem. C 2008, 112, 13264), a more detailed picture of the electrochromic switching mechanism in this kind of compound was proposed. It was demonstrated that the changeover mechanism is closely related to the electrochromic process. Specifically, it was shown that the coloring process is related to the changeover. Furthermore, by means of spectra-electrochemistry measurements in complement with the insoluble structural characteristics of the compound, it was proposed that the electronic charge preferentially occupies Fe3+(NC)(5)OH- clusters (i.e., pentacoordinated Fe3+ sites). All of these sites represent 25% of the total charge amount capable of being injected in the hexacyanometallate compounds. This is exactly the compositional point where the material starts bleaching and where the changeover is activated. After this compositional point, the Fe3+ sites of Fe2+-CN-Fe3+ chains (hexacoordinated Fe3+ sites) begin to be occupied so that the polaronic mechanism responsible for the strong blue color of the compound is suppressed at this compositional point, and accordingly, the FeHCF is suddenly bleached, accompanied by a current peak that defines the changeover process.